Method for preparing super-hydrophobic surface on bipolar plate of hydrogen fuel cell
The superhydrophobic surface is prepared on stainless steel plates through nanosecond laser etching and chemical modification technology, which solves the corrosion and performance problems of hydrogen fuel cell bipolar plates in harsh environments, and achieves efficient conductivity and corrosion resistance, improving The output performance and service life of hydrogen fuel cells are achieved.
Patent Information
- Application Number
- CN202411294272.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-14
- Publication Date
- 2024-12-17
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The hydrogen fuel cell bipolar plate is prone to corrosion in high humidity, high potential and high acid environments, resulting in reduced performance and shortened service life. In addition, the traditional graphite bipolar plates lack electrical conductivity and thermal conductivity, and the metal bipolar plates release Fe after corrosion. , Cr and Ni ion contamination catalysts affect conversion efficiency.
Nanosecond laser etching technology is used to prepare superhydrophobic surfaces on stainless steel plates to form a multi-stage array structure, and combined with stearic acid ethanol solution modification, to obtain stainless steel materials with excellent conductivity, corrosion resistance and frost resistance.
It realizes superhydrophobicity in a wide temperature range, reduces the cold start response time of hydrogen fuel cell, improves conductivity and corrosion resistance, meets the strict performance indicators of hydrogen fuel cell bipolar plates, and alleviates water vapor condensation and frosting problems.
Smart Images

Figure CN119153719A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of powder metallurgy, and in particular to a method for preparing a super-hydrophobic surface on a bipolar plate of a hydrogen fuel cell. Background Art
[0002] The automotive industry consumes a large amount of fossil fuels, which has exacerbated the global environmental and energy crisis. As a new generation of energy technology, hydrogen fuel cells have broad application prospects as a source of automotive power due to their clean, pollution-free and renewable characteristics.
[0003] Hydrogen fuel cells are usually composed of bipolar plates (Bipolar Plate, BPP), membrane electrode assembly (Membrane Electrode Assembly, MEA), sealing gaskets and end plates. Bipolar plates are one of the important components of hydrogen fuel cells, accounting for a large part of the mass and cost of the battery, and are responsible for the distribution of reaction gases, current conduction, drainage and heat dissipation. Traditional graphite bipolar plates have the disadvantages of large thickness, low battery volume power ratio and high processing cost due to the low bending strength of graphite and the high brittleness of the material. Under the high operating temperature of hydrogen fuel cells, the polymer materials of graphite composite bipolar plates may degrade and ion seepage may occur, thus affecting the performance of hydrogen fuel cells. Compared with graphite bipolar plates, metal bipolar plates have excellent electrical conductivity, thermal conductivity, gas barrier and mechanical properties. Under the same power, the volume of metal bipolar plate hydrogen fuel cells will be smaller than that of graphite bipolar plate hydrogen fuel cells, and the power density will be higher. Therefore, metal bipolar plates are considered to be candidates for the new generation of hydrogen fuel cell bipolar plates.
[0004] The working conditions of hydrogen fuel cells are complex and their working environment is harsh, under high humidity, high potential, high acidity (pH2-3), and relatively high temperature (60-80°C). In the working environment of hydrogen fuel cells, metal bipolar plates are susceptible to corrosion, forming a passivation film on their surface, which significantly increases the interfacial contact resistance between the metal bipolar plates and the gas diffusion layer. Moreover, the Fe, Cr, and Ni ions released after the metal bipolar plates are corroded will contaminate the catalyst and poison the membrane electrode, ultimately leading to a decrease in the conversion efficiency of the hydrogen fuel cell. This reduces the output performance of the hydrogen fuel cell and shortens its service life. Therefore, it is urgent to provide a method for preparing a corrosion-resistant material. Summary of the invention
[0005] In order to develop a method for preparing a corrosion-resistant material, the present invention provides a method for preparing a super-hydrophobic surface on a hydrogen fuel cell bipolar plate. The stainless steel material provided by the present invention has a super-hydrophobic surface, good electrical conductivity, excellent corrosion resistance, and good frost resistance, and is a high-quality material for preparing electrodes of hydrogen fuel cell monomers.
[0006] The present invention provides a method for preparing a super-hydrophobic surface on a hydrogen fuel cell bipolar plate, comprising the following steps:
[0007] Pretreatment of stainless steel plate: Use stainless steel plate as substrate, polish the surface with sandpaper, then ultrasonically clean it in deionized water for 10min to 15min, then ultrasonically clean it in ethanol for 10min to 15min, and after drying, obtain a stainless steel plate with a smooth surface for standby use;
[0008] Nanosecond laser etching of multi-level rough surface: Use nanosecond infrared laser to process and etch patterns in the horizontal and vertical directions on the smooth stainless steel plate, ultrasonically clean it, and then soak it in stearic acid ethanol solution for 4h to 5h, and then dry it to obtain a stainless steel material with a super-hydrophobic surface;
[0009] The laser parameters are set as follows: the laser scanning speed is 180 mm·s -1 ~200mm·s -1 The laser repetition frequency is 15kHz~20kHz, and the average output power is 30W~35W.
[0010] Furthermore, the sandpaper polishing process is: polishing the surface of the stainless steel plate with 400#, 600#, 800#, and 1000# sandpapers in sequence.
[0011] Furthermore, the drying parameters of the pretreatment process of the stainless steel plate are: drying at 80° C. to 85° C. for 9 min to 10 min.
[0012] Furthermore, the laser scanning speed, laser repetition frequency and average output power are set to 200 mm·s -1 , 20kHz and 30W.
[0013] Furthermore, the ultrasonic cleaning process after nanosecond laser etching of the multi-level rough surface is: ultrasonic cleaning in deionized water for 10 minutes to 15 minutes, and then ultrasonic cleaning in ethanol for 10 minutes to 15 minutes.
[0014] Furthermore, the stearic acid ethanol solution is 1.0wt% to 2.0wt%.
[0015] Furthermore, the drying process after nanosecond laser etching of the multi-level rough surface is: drying at 80° C. to 85° C. for 30 min to 40 min.
[0016] Furthermore, the parameters for equally spaced etching patterns in the horizontal and vertical directions on the stainless steel plate with a smooth surface are: the marking interval is 0.03 mm to 0.09 mm, the pattern center point interval is 0.03 mm to 0.09 mm, and the number of repeated processing times is 1 to 7 times.
[0017] Furthermore, the super-hydrophobic surface presents a multi-peak rough structure with pores and nipple-like island structures at the micrometer or nanometer scale.
[0018] Furthermore, the super-hydrophobic surface is used to prepare metal bipolar plates in hydrogen fuel cell cells, thereby improving the conductivity, corrosion resistance and frost resistance of the electrodes.
[0019] Compared with the prior art, the present invention has the following beneficial effects:
[0020] The present invention is based on nanosecond laser etching, and proposes a method for preparing a stainless steel material with a super-hydrophobic and corrosion-resistant surface that is simple, easy to use, low-cost, and recyclable. By cleverly utilizing the disadvantages of the thermal effect of nanosecond lasers, using different laser etching pattern parameters and repeated processing times, a multi-level array structure with hundreds of nanometers to tens of microns is formed on the stainless steel surface. The prepared SH-SSP has good hydrophobicity (contact angle greater than 120°) in a wide temperature range (-15 to 85°C), and has good anti-icing and anti-frost properties. The prepared SH-SSP also has excellent electrical conductivity and corrosion resistance, meets the most stringent performance indicators of hydrogen fuel cell bipolar plates, can alleviate the problems of water vapor condensation and frosting inside the flow channels of hydrogen fuel cell bipolar plates, and reduce the cold start response time of hydrogen fuel cells in extreme environments. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0022] Figure 1 SEM images of the stainless steel material SH-SSP fabrication process by laser etching;
[0023] In the figure, (a) is a schematic diagram of laser-etched graded rough structure;
[0024] (b) Schematic diagram of laser etching processing path and parameters;
[0025] (c) Schematic diagram of the relationship between the characteristics of micro-spikes formed by laser etching;
[0026] (d) SEM image of SH-SSP at a scale of 100 μm.
[0027] (e) SEM image of SH-SSP with a scale bar of 10 μm;
[0028] (f) SEM image of SH-SSP with a scale bar of 5 μm;
[0029] (g) is the optical cross-section of the prepared SH-SSP;
[0030] (h) is the appearance of the original material SSP;
[0031] (i) is the appearance diagram of the stainless steel material SH-SSP prepared in the present invention.
[0032] Figure 2 is the actual contact angle and fractal dimension of the SSP sample;
[0033] In the figure, (a) shows the actual contact angle and fractal dimension of the sample with different laser repetition processing times;
[0034] (b) The actual contact angle and fractal dimension of samples with different marking intervals.
[0035] Figure 3 To test the cold resistance of super hydrophobic bipolar plate samples;
[0036] In the figure, (a) is the room temperature contact angle of different samples of 3-0.05 sample frozen and not frozen at -18℃ for 12h.
[0037] (b) Room temperature contact angles of different samples of 5-0.05 sample frozen and not frozen at -18 °C for 12 h;
[0038] (c) Changes in contact angles of SSP-0, 3-0.05 and 5-0.05 samples at different temperatures;
[0039] (d) Anti-icing performance of SSP-0, 3-0.05 and 5-0.05 samples;
[0040] (e) is the anti-frost performance of SSP-0, 3-0.05 samples and 5-0.05 samples.
[0041] Figure 4 To detect the volume resistivity of superhydrophobic bipolar plate samples;
[0042] In the figure, (a) is the volume resistivity of SSP-0 and SH-SSP 5-0.05;
[0043] (b) Interface contact resistance curves of SSP-0 and SH-SSP 5-0.05;
[0044] (c) Contact angle and thickness of SH-SSP 5-0.05 at room temperature after regeneration cycle test;
[0045] (d) The contact angles of SH-SSP 5-0.05 at different temperatures before and after the regeneration cycle experiment, when frozen / unfrozen at -18 °C for 12 h.
[0046] (e) Polarization curves of SSP-0 and SH-SSP 5-0.05 in 3.5wt% NaCl solution;
[0047] (f) SEM images of SSP-0 and SH-SSP5-0.05 after potentiodynamic polarization test.
[0048] Figure 5 For the simulation application of super hydrophobic 316L metal bipolar plate;
[0049] In the figure, (a) is a hydrogen fuel cell assembled from laser-etched super-hydrophobic 316L metal bipolar plates;
[0050] (b) is a schematic diagram of a visualization observation platform for water flow in the flow channel of a super-hydrophobic metal bipolar plate;
[0051] (c) To simulate the normal temperature operating conditions of hydrogen fuel cells, the half-electrode water flooding test of hydrogen fuel cells;
[0052] (d) To simulate the low temperature working conditions of hydrogen fuel cells, the hydrogen fuel cell half-electrode frost protection test is performed.
[0053] Figure 6 SEM images of laser etched patterns at different magnifications;
[0054] In the figure, (a) is the SEM image of sample 1-0.05 at different magnifications, and the scale bars from left to right are 100μm, 10μm, and 5μm;
[0055] (b) is the SEM image of sample 3-0.05 at different magnifications. The scale bars from left to right are 100 μm, 10 μm, and 5 μm respectively.
[0056] (c) is the SEM image of sample 7-0.05 at different magnifications. The scale bars from left to right are 100μm, 10μm, and 5μm, respectively.
[0057] Figure 7 Optical profiles of three samples: 1-0.05, 3-0.05, and 7-0.05;
[0058] In the figure, (a) is the optical profile of sample 1-0.05;
[0059] (b) is the optical profile of sample 3-0.05;
[0060] (c) is the optical profile of sample 7-0.05.
[0061] Figure 8 XPS analysis of SSP and SH-SSP;
[0062] In the figure, (a) is the XPS analysis of SSP;
[0063] (b) XPS analysis of SH-SSP.
[0064] Fig. 9 AFM analysis of smooth substrate, super-hydrophobic sample and super-hydrophobic sample after freezing;
[0065] In the figure, (a) is the AFM analysis of a smooth substrate;
[0066] (b) is the AFM analysis image of the super-hydrophobic sample;
[0067] (c) is the AFM analysis image of the superhydrophobic sample after freezing. DETAILED DESCRIPTION
[0068] The specific embodiments of the present invention are described in detail below, but it should be understood that the protection scope of the present invention is not limited by the specific embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work belong to the scope of protection of the present invention. The experimental methods described in the embodiments of the present invention are conventional methods unless otherwise specified, and the materials, reagents, etc. used in the following embodiments can be obtained from commercial channels unless otherwise specified. All chemical reagents involved in the present invention are commercially available chemical reagents and can be used directly without any post-treatment.
[0069] Example 1: A method for preparing a stainless steel material.
[0070] 1. Experimental Methods
[0071] 1. Preparation steps of stainless steel material SH-SSP:
[0072] (1) Pretreatment of 316L stainless steel plate
[0073] A commercial 316L stainless steel plate (20mm×20mm×3mm) was used as the substrate. Before laser treatment, the stainless steel plate was polished with 400#, 600#, 800#, and 1000# sandpaper to obtain a relatively smooth surface. The polished stainless steel plate was cleaned in deionized water and ethanol by an ultrasonic machine for 15 minutes each.
[0074] Finally, the cleaned stainless steel plate was dried in a forced air drying oven (101-0B, Supo Instrument Co., Ltd., Shaoxing, China) at 80 °C for 10 min for subsequent surface treatment and characterization.
[0075] (2) Preparation of multi-level rough surfaces by nanosecond laser etching
[0076] Superhydrophobic surfaces were prepared on 316L steel by combining laser etching treatment and subsequent low surface energy material modification. First, a nanosecond infrared laser fiber machine with a laser wavelength of 1064 nm (FB30-1, Changchun New Industry Optoelectronics Technology Co., Ltd., Changchun, China) was used to process laser etching patterns with different marking spacings in the horizontal and vertical directions of the sample. The specific parameters of the laser etching patterns are shown in Table 1. According to the marking spacing and the number of repeated processing, the laser etched samples were marked as 1-0.05, 3-0.05, 5-0.05, 5-0.05, 7-0.05, 5-0.03, 5-0.07, and 5-0.09, respectively. In addition, the laser scanning speed, laser repetition frequency, and average output power were set to 200 mm·s, respectively. -1 , 20kHz and 30W. After laser processing, the sample was cleaned with deionized water and anhydrous ethanol by ultrasonic for 15 minutes each, and then immersed in 1.0wt% stearic acid ethanol solution for 4 hours. Finally, the sample was placed in a blast drying oven and dried at 80℃ for 40 minutes to complete the preparation of the super hydrophobic surface of the 316L stainless steel sample.
[0077] Table 1 Laser etching patterns and parameters on 316L stainless steel surface
[0078] sample Marking spacing s(mm) Pattern center point spacing p(mm) Repeat processing times 1-0.05 0.05 0.05 1 3-0.05 0.05 0.05 3 5-0.05 0.05 0.05 5 7-0.05 0.05 0.05 7 5-0.03 0.03 0.03 5 5-0.07 0.07 0.07 5 5-0.09 0.09 0.09 5
[0079] 2. Surface, microstructure and wettability characterization
[0080] Field emission scanning electron microscopy (FIB-SEM, LYRA 3XMH, TESCAN, Czech) and energy dispersive spectroscopy (EDS, Oxford INCA Energy) were used to analyze the surface morphology and elemental composition of the prepared samples. X-ray photoelectron spectroscopy (XPS, AXIS Ultrabld, Kratos) with an Al kα source was used to analyze the surface chemical state and bonding structure of the prepared samples. The three-dimensional morphology of the prepared samples was characterized by ultra-depth microscopy (DVM6, Leica, Germany). The wetting properties of the substrate and the prepared samples were measured by a contact angle meter (JY-82C, Chengde Dingsheng Testing Machine Inspection Equipment Co., Ltd., Hebei, China). During the wetting test, a 4μl deionized water droplet was squeezed out at 4 locations on the sample with a micro syringe and the average value was taken.
[0081] 3. Performance Characterization
[0082] (1) Anti-icing and anti-frost performance
[0083] The anti-frosting behavior of the sample and the static freezing of water droplets were studied on a semiconductor refrigeration plate. The freezing and anti-frosting state of water droplets on the sample surface were observed using a stereo microscope (SZ680TP, Chongqing Aote Optical Instrument Co., Ltd., Chongqing, China) and a high-definition camera (EOS M6 MarkⅡ, Canon, China). In the anti-frosting and anti-icing experiments, the sample temperature was always kept at -15±2℃. The ambient temperature was 20±2℃, and the corresponding humidity was 40±5%.
[0084] (2) Electrical conductivity
[0085] The bulk resistance and interfacial contact resistance (ICR) are important parameters that determine the performance of bipolar plates. The four-probe method was used to measure the bulk resistance of the sample. A linear four-probe method was used, where S = 1mm and C = 6.28. The voltage of the metal bipolar plate was measured using a Keithley digital source meter with a constant current (0.628A). The bulk resistance was calculated based on the voltage and current. The interfacial contact resistance of the sample was measured according to the Davies method.
[36] Before the test, the sample was placed between two pieces of carbon paper to simulate the contact between the bipolar plate and the gas diffusion layer, and then the sandwich structure of carbon paper / sample / carbon paper was placed between two copper plates. The sample resistance was recorded by a Keithley digital source meter as the load pressure increased from 0 to 240 N·cm -2 changes.
[0086] (3) Corrosion resistance
[0087] The corrosion test was carried out in 3.5 wt% NaCl solution at room temperature using an electrochemical workstation (CHI 660E, Shanghai Huachen Instrument Co., Ltd., Shanghai, China). The Pt electrode, saturated calomel electrode (SCE) and the sample were used as the counter electrode, reference electrode and working electrode, respectively. The sample was connected with a copper wire and then sealed with silicone rubber, leaving a 1×1 cm 2 The exposed area is used for corrosion test. First, the sample is immersed in 3.5wt% NaCl solution for 20min for OCP (open circuit potential) test to ensure the potential is stable. Then the potentiodynamic polarization test is carried out, the voltage is set in the range of ±0.5V (VS.OCP), and the scanning rate is 1mV·s -1 According to the measured Tafel diagram, the corrosion potential and corrosion current density can be obtained. Polarization resistance R p It can also be calculated using the Ster-Geary equation:
[0088]
[0089] In the formula, j corr Refers to the corrosion current density, β a and β care the slopes of the anode and cathode Tafel curves.
[0090] (4) Bipolar plate flow channel experiment
[0091] The normal operating temperature of hydrogen fuel cells is 60-80℃, but in the cold north, the outdoor temperature can reach above -10℃ in winter. When the hydrogen fuel cell starts to start at low temperature, water gradually forms at the cathode of the battery. When the temperature inside the battery is not high enough to reach the melting point of ice, ice will form inside the hydrogen fuel cell, causing the voltage to drop and stop working. In order to effectively improve the cold start performance of the fuel cell, the working conditions of the hydrogen fuel cell are simulated, and the serpentine flow channel is laser processed on the 316L stainless steel plate to simulate different working conditions and observe the water distribution in the flow channel.
[0092] 2. Experimental Results
[0093] 1. Surface morphology and chemical composition
[0094] During the laser processing of metal materials, the electrons on the surface of the material undergo thermal motion under the action of external energy, causing the temperature of the material to rise sharply. When the temperature of the material reaches the melting point, it melts and forms a molten pool. As the laser continues to heat the material, the temperature of the material continues to rise as the material absorbs more energy. After absorbing a certain amount of heat, it reaches the vaporization temperature, the material is vaporized and evaporated, and part of the material disappears, forming micro-pits. The metal material fragments produced by the plasma plume around the laser impact and the spot re-accumulate around the micro-pits to form protrusions. This phenomenon can form structures with a scale of nanometers to micrometers, which coincides with the synaptic size of the lotus leaf surface (200nm-5μm). The reaction process is as follows: Figure 1 As shown in a.
[0095] The present invention is used Figure 1 In the method (b), by punching out array points, four adjacent light spots are used to form synapses. The size of the synapse is related to the light spot and the parameters s and p. s is the marking spacing, and p is the spacing between the center points of the laser etching pattern. Thus, a synapse array with multi-level scale roughness is obtained, such as Figure 1 The SEM image of the laser etched pattern 5-0.05 stainless steel after surface chemical modification by 1.0wt% stearic acid ethanol solution is shown in Figure 1 (c)- Figure 1 As shown in (f). Figure 1 (d) and Figure 1 From (g), the laser-etched steel surface presents a typical multi-peak rough structure; Figure 1 From (e), it can be seen that the laser-etched steel surface has a large number of pores and nipple island structures at the micron / nano scale. Figure 1From the (f), fibrous and spherical particles and aggregates can be clearly identified on the surface of the sample after laser etching. This special structural morphology makes the laser-etched sample surface an ideal candidate for obtaining superhydrophobic properties. SEM images of other laser-etched patterns at different magnifications ( Figure 6 ) It can also be seen that the laser-etched steel surface presents a typical multi-peak rough structure with a large number of pores and nipple-like island structures at the micrometer / nanometer scale. Figure 1 (h)- Figure 1 (i) are digital images of droplets on the surface of original 316L stainless steel and chemically modified 5-0.05 sample. It can be clearly seen that the water droplets did not spread on the surface of the 5-0.05 sample, but presented a relatively complete spherical shape, indicating that the 5-0.05 sample has extremely strong water resistance and becomes superhydrophobic after chemical modification.
[0096] 2. EDS and XPS elemental analysis
[0097] The original smooth 316L stainless steel substrate and the super-hydrophobic samples before and after laser etching were analyzed by EDS and XPS. The EDS images of the smooth substrate and the laser-etched sample 5-0.05 are shown in Figure 2. Figure 8 As shown in the figure, obvious changes in Fe, C, and O elements were detected, which revealed that the material surface was oxidized under laser irradiation, just as expected for the oxidation reaction of hot / molten metal with air. In order to further systematically study the effect of chemical modification on the surface of laser-etched samples, the samples modified with stearic acid ethanol solution were further characterized by XPS. The analysis results are shown in Figure 2. Figure 8 And as shown in Table 2.
[0098] Table 2 Elemental composition obtained by XPS analysis
[0099] C O Fe Cr Ni Pristine 41.64 45.13 7.88 5.35 - Laser Treated 33.11 50.76 10.83 2.88 2.42 SA Treated 70.72 22.63 3.92 1.65 1.08
[0100] For the untreated SS sheet, four elements, Fe, Cr, O, and C, were detected on the XPS surface. The asymmetric peak of Fe at 706.4eV is Fe elemental, and the appearance of multiple split peaks and satellite peaks around 710eV indicates that the surface Fe is in the III valence state. The single peak of Cr at 574.3eV is Cr elemental, and the multiple peaks between 574-580eV are CrIII oxides; Ni was not detected because of the presence of Cr and Fe oxide layers on the SS surface; the C and O on the surface mainly come from contaminated carbon and CO2 adsorbed on the surface; after the SS is laser treated, it can be seen that the valence state and content of the surface C element have basically not changed (XPS+EDS), while the oxygen content has increased significantly (EDS). According to the O1s data, the relative content of the metal oxide peak at around 529.5 has increased after laser treatment. This is because the high energy of the laser etching process heats the local area to a high temperature, generates a plasma plume on the local surface, and the SS under the surface is melted and oxidized to form Figure 1 The multi-level nanostructure shown in the figure also produces more metal oxides. Comparing the corresponding XPS spectra of Fe and Cr, it can be seen that the content of Fe(III) and Cr(III) oxides has increased significantly. At the same time, it was found that the signal of Ni oxide was also detected in the Ni spectrum. This shows that laser processing enriches more metal oxide products on the SS surface. On the one hand, these products can produce a certain passivation effect (anti-corrosion results), and on the other hand, they also make the SS surface more conducive to the modification of SA, thereby reducing the chemical energy of the SS surface. SA is stearic acid (C 18 H 36 O2), the carboxyl group at one end can react with the oxide on the metal surface to form a self-assembled layer, and its hydrophobic tail can be arranged in a directional parallel manner to form a hydrophobic layer on the surface of the material. Compared with the flat SS plate, the SS sheet after laser etching in this paper has more metal oxide reaction sites on the surface, and it also has a multi-level surface structure. Therefore, after modifying SA, the hydrophobicity of the SS surface can be significantly enhanced.
[0101] Therefore, it was demonstrated that stearic acid molecules were successfully grafted onto the textured steel surface and formed a self-assembled coating through this simple impregnation process.
[0102] 3. Wetting behavior of chemically modified laser-etched 316L stainless steel
[0103] The wetting properties of materials are mainly determined by their surface morphology and chemical composition. The contact angle measurements of 316L stainless steel smooth substrate SSP-0 sample, laser etched 5-0.05 sample, and chemically modified 5-0.05 sample are shown in Figure 2. Figure 2 As shown in (a). Figure 2(a) shows that the smooth substrate SSP-0 shows a little hydrophilicity with a contact angle of 86.74°. When a multi-level rough pattern is made on the steel surface, the surface of the laser-etched 5-0.05 sample becomes more hydrophilic, and the contact angle is almost close to 0°. This phenomenon is consistent with Wenzel's wetting mold, that is, the increased rough surface can further enhance the hydrophilicity of the hydrophilic surface. When the laser-etched surface is further modified by the low surface energy material stearic acid, such as Figure 2 As shown in (a), the surface of the 5-0.05 sample exhibits excellent water repellency, and the contact angle increases to 151.74° to achieve superhydrophobicity. When a series of multi-level rough patterns are manufactured on the sample surface, its surface exhibits multi-level roughness, which is essential for obtaining superhydrophobic properties. Therefore, when the laser-etched surface is further modified with low surface energy material stearic acid, it becomes superhydrophobic. This superhydrophobic property is caused by the synergistic effect of laser-etched multi-level rough surface morphology and chemical modification. The wetting model of the superhydrophobic surface is described by the Cassie-Baxter wetting model, as shown in the following formula:
[0104]
[0105] In the formula, θ c is the contact angle of the rough surface, f s is the solid fraction, L is the maximum size of the fractal structure on the sample surface, l is the minimum size of the fractal structure on the sample surface, σ SG is the solid-gas surface tension, σ SL is the solid-liquid surface tension, σ LG is the liquid-gas surface tension.
[0106] Figure 2 (a) is the contact angle and fractal dimension of four samples 1-0.05, 3-0.05, 5-0.05, and 7-0.05 obtained by different laser repetition times. Figure 2 (b) shows the contact angle and fractal dimension of the four samples of 5-0.03, 5-0.05, 5-0.07, and 5-0.09 obtained by using different laser marking spacings. And the optical profiles of the three samples of 1-0.05, 3-0.05, and 7-0.05 are shown in Figure 7 As shown. Three different areas of the same sample SEM surface were extracted, and the fractal dimension D was calculated using MATLAB (R2017b, MathWorks, Natick, US) software and the average value was taken. The solid fraction f was obtained by analyzing the optical contour map of the sample. s , based on the fractal dimension D, the maximum size L, the minimum size l, and the fraction f sThe theoretical contact angle of the sample is obtained by using the parameters such as the actual contact angle and the theoretical contact angle. The detailed parameter values such as the actual contact angle and the theoretical contact angle are listed in Table 3. Through the analysis of the results in Table 2, the errors between the actual contact angle and the theoretical contact angle of different samples are all within 1%, indicating that the measured contact angle is effective. Specifically, when s and p are 0.05 mm, the number of laser repetitions is 5 times, the fractal dimension of the 5-0.05 sample is the largest, the solid fraction is the smallest, and it exhibits superhydrophobic properties when further modified by the low surface energy material stearic acid. If a superhydrophobic surface is constructed on the sample surface, appropriate laser processing parameters should be selected so that the sample has anti-icing / frost and anti-corrosion properties.
[0107] Table 3 Specific values of theoretical contact angle and actual contact angle of different samples
[0108]
[0109]
[0110] 4. Anti-icing and anti-frost performance
[0111] According to Fourier's law, the heat transfer Q between the surface and the water droplet is related by
[40] :
[0112]
[0113] Where T1 and T2 are the temperatures of the droplet and the surface, K is the heat transfer coefficient, and S is the solid-liquid contact area. Therefore, Q is proportional to S. The trapped air between the droplet and the rough superhydrophobic surface structure reduces the solid-liquid interface. Less heat is transferred from the droplet to the superhydrophobic surface, which causes the freezing process to be much longer than the substrate. Frost plays a vital role in the freezing of droplets, and the frost front acts as a seed to induce the freezing of droplets (micro and macro) when in close contact. Anti-icing and anti-frost results show that the superhydrophobic sample 5-0.05 has better anti-icing and anti-frost properties than other surfaces.
[0114] Figure 3 (a)- Figure 3 (b) shows the contact angles of samples with different laser etching parameters before and after freezing at -18°C at room temperature. It can be seen from the figure that after freezing, the contact angles of all samples have decreased. The room temperature contact angle of the 5-0.05 super-hydrophobic sample after freezing is 149.44°, which is close to the super-hydrophobic state. Through the AFM analysis of smooth substrates, super-hydrophobic samples and super-hydrophobic samples after freezing ( Fig. 9), the sample morphology has slight changes after freezing, but the changes are not significant. It may be that the slight changes in the morphology and surface coating after freezing caused the decrease in the contact angle of the sample after freezing. The wettability changes of the smooth substrate, 3-0.05 sample, and 5-0.05 sample in the range of -15-85℃ before and after freezing and not freezing at -18℃ for 12h are shown in the figure. Figure 3 (c) is shown. In the range of 25-85℃, the contact angles of different samples decrease with increasing temperature. This is because as the temperature increases, the air flow in the air pockets on the surface of the laser-etched sample accelerates, causing the sample surface to transition from the Cassie state to the Cassie-Wenzel state, resulting in a decrease in the contact angle. In the range of -15 to 25℃, it can be observed that the contact angle of the tested sample is linearly related to the decrease in temperature. This behavior is attributed to the condensation of water on the surface of the material at temperatures slightly above 0℃, resulting in the so-called Cassie-Wenzel state, which leads to a decrease in the contact angle. As the temperature decreases further, due to the formation of ice nuclei from the gas phase at 0℃, frost forms on the sample surface, resulting in a loss of superhydrophobicity. Compared with the smooth substrate sample, the contact angle of the laser-etched sample can still be maintained above 140° in the temperature range of -15 to 85℃ before and after the laser-etched sample is frozen. At 85°C, the contact angles of the superhydrophobic sample before and after freezing treatment were 144.63° and 143.92°; at -15°C, the contact angles of the superhydrophobic sample before and after freezing treatment were 142.6° and 140.11°, which were significantly higher than the contact angles of other samples under the same conditions.
[0115] The static freezing process of water droplets on the smooth substrate sample SSP-0, the hydrophobic sample 3-0.05 surface and the super-hydrophobic sample 5-0.05 surface was observed by using a semiconductor refrigeration plate and a stereo microscope. Figure 3 As shown in (d). A 4μl water droplet was dropped on the sample surface, the sample temperature was maintained at -15±2℃, the ambient temperature was 20±2℃, and the corresponding humidity was 40±5%. Through observation, the water droplets on the surface of the smooth substrate SSP-0 sample began to freeze at 270s, the water droplets on the surface of the hydrophobic sample 3-0.05 began to freeze at 917s, and the water droplets on the surface of the super-hydrophobic sample 5-0.05 began to freeze at 2357s. Comparing the freezing time of water droplets on the three surfaces, the super-hydrophobic surface has a longer freezing time than other surfaces, and the freezing of water droplets on the smooth substrate is delayed by about 35 minutes.
[0116] The frosting process of the smooth substrate sample SSP-0, the hydrophobic sample 3-0.05 surface and the super-hydrophobic sample 5-0.05 surface was observed by a semiconductor refrigeration plate and a high-definition camera. Figure 3As shown in (e). The sample temperature was maintained at -15±2℃, the ambient temperature was 20±2℃, and the corresponding humidity was 40±5%. Through observation, the smooth substrate sample SSP-0 showed a large frosting phenomenon at 297s, while the surfaces of other samples did not show any frosting; at 585s, the surface of the hydrophobic sample 3-0.05 began to frost, while the superhydrophobic sample 5-0.05 did not show any frost, and the surface of the smooth substrate sample SSP was completely frosted; at 1183s, a large frosting phenomenon appeared on the surface of the superhydrophobic sample 5-0.05, and the frosting area was significantly smaller than that of the hydrophobic sample 3-0.05; at 25min, the surface of the hydrophobic sample 3-0.05 was completely frosted, while the surface of the superhydrophobic sample 5-0.05 was not completely frosted. The time taken for the surface of the superhydrophobic sample 5-0.05 to frost was significantly longer than that of other surfaces, which is consistent with the above-mentioned anti-icing performance.
[0117] 5. Other properties of the prepared stainless steel material
[0118] (1) Electrical conductivity
[0119] Bulk resistance and interfacial contact resistance (ICR) are important parameters that determine the performance of bipolar plates. Higher bulk resistance and interfacial contact resistance will increase the power consumption of hydrogen fuel cells and shorten their service life.
[36] . Generally, if a sample exhibits excellent conductivity, its bulk resistance and interfacial contact resistance (ICR) values are both small. The four-probe method was used, with linear four-probes, S = 1mm, C = 6.28, and the voltage was measured by a Keithley digital source meter using a constant current (0.628A). The bulk resistance was calculated based on the voltage and current. The bulk resistance of the 316L smooth substrate SSP-0 and the superhydrophobic sample 5-0.05 was studied, and the results are as follows Figure 4 As shown in (a), the volume resistivity values of the smooth substrate SSP-0 and the superhydrophobic sample 5-0.05 are 6.31×10 -7 Ohm·m and 5.82×10 -7 Ohm·m, and their corresponding conductivity are 1.58×10 4 S cm -1 and 1.72×10 4 S cm -1 , meeting the US Department of Energy (DOE) 2025 conductivity> 100S·cm -1 performance requirements.
[0120] The interfacial contact resistance between 316L smooth substrate SSP-0 and superhydrophobic sample 5-0.05 and carbon paper was studied under different pressing forces. The results are shown in Figure 2. Figure 4(b) shows that the interfacial contact resistance of the sample decreases sharply with the increase of the pressing force at the beginning, and then decreases slowly until it reaches a stable value. This is because the actual contact area between the interfaces increases with the increase of the pressing force, resulting in an increase in conductivity. The interfacial contact resistance of the smooth substrate SSP-0 and the superhydrophobic sample 5-0.05 at 2.4MPa is 18.43mΩ·cm 2 and 8.42 mΩ·cm 2 The interface contact resistance of the super-hydrophobic sample 5-0.05 at 1.5 MPa is 9.816 mΩ·cm 2 , meeting the US Department of Energy (DOE) 2025 contact resistance ≤ 10mΩ·cm 2 (Clamping force 1.5MPa) performance requirements.
[0121] (2) Regeneration cycle experiment
[0122] Artificial superhydrophobic surfaces are relatively fragile and may lose their water repellency due to scratches or abrasion, causing adverse damage to the surface chemistry and structure. In practical applications, superhydrophobic surfaces are inevitably damaged and lose their superhydrophobicity. Here, a regeneration test is proposed to verify whether the laser-etched superhydrophobic surface can be restored to superhydrophobic properties after sandpaper polishing using the same superhydrophobic surface preparation method. Figure 4 (c) is the change of contact angle and sample thickness of 316L stainless steel super hydrophobic sample 5-0.05 in 5 reciprocating cycles. After 316L stainless steel substrate was polished and cleaned with 400#, 600#, 800#, and 1000# sandpaper, the contact angle was measured to be 86.74° and the thickness was 2.65mm. The same method was used to prepare the super hydrophobic sample, and the sample contact angle was measured to be 151.74° and the thickness was 2.62mm. The laser texture surface of the sample was polished off with 240# sandpaper, and then the super hydrophobic sample was prepared in the same way. The sample contact angle of the second cycle experiment was measured to be 150.98° and the thickness was 2.48mm. The next cycle experiment uses the same steps as above. The contact angle of the sample in the third cycle experiment is 150.23° and the thickness is 2.32mm; the contact angle of the sample in the fourth cycle experiment is 149.31° and the thickness is 2.19mm; the contact angle of the sample in the fifth cycle experiment is 150.4° and the thickness is 2.05mm. According to the experimental results, the sample can still maintain super hydrophobicity after each cycle experiment. After 5 cycles, the thickness is only reduced by 0.6mm compared with the initial sample, which is kept within a controllable range. Figure 4 (d) is the change in contact angle at various temperatures measured before and after the superhydrophobic sample 5-0.05 regeneration cycle experiment, under the conditions of freezing and not freezing at -18℃ for 12h. Figure 4According to the analysis of (d), the contact angle decreased by 1° after the regeneration cycle experiment at 25°C. Within 25°C-85°C, the difference in contact angle before and after the regeneration cycle experiment was within 0-3°; within -15°C to 25°C, the difference in contact angle before and after the regeneration cycle experiment was within 4-7°. The contact angle before and after the regeneration cycle experiment did not change much, and it can still maintain a high hydrophobic performance, making it more promising in industrial applications.
[0123] (3) Corrosion resistance
[0124] Potentiodynamic polarization test has been used to evaluate the transient corrosion behavior of metal materials and the corrosion protection ability of protective superhydrophobic coatings. The potentiodynamic polarization curves of 316L stainless steel smooth substrate SSP-0 and superhydrophobic sample 5-0.05 in 3.5wt% NaCl solution are shown in Figure 2. Figure 4 As shown in (e), its specific potential electrokinetic results and corrosion inhibition rates are listed in Table 4. It can be clearly seen from the potentiodynamic polarization curve that the corrosion potential of the superhydrophobic sample 5-0.05 moves in the positive direction, indicating that its corrosion resistance has improved. In addition, the potentiodynamic polarization curve also moves to the left, resulting in a decrease in current density.
[0125] like Figure 4 As shown in (e), it is obvious that the corrosion potential of the superhydrophobic sample 5-0.05 moves in the positive direction, indicating that its corrosion resistance has improved. In addition, the potentiodynamic polarization curve also moves to the left, indicating that its current density decreases. Corrosion current density is generally regarded as an important parameter for evaluating corrosion resistance. The lower the corrosion current density, the better the corrosion resistance. According to the potentiodynamic results analysis in Table 2, the corrosion potential E of the 316L stainless steel smooth substrate SSP-0 corr and corrosion current density j corr -0.3Vvs.SCE and 0.197μA·cm -2 , the corrosion potential E of the superhydrophobic sample 5-0.05 corr and corrosion current density j corr -0.161Vvs.SCE and 0.819μA·cm -2 The superhydrophobic sample 5-0.05 exhibits a higher corrosion potential value and a lower corrosion current density value. In addition, the polarization resistance R p It is also widely used to evaluate the corrosion resistance of materials. It comprehensively considers the effects of corrosion current density and Tafel curve. The polarization resistance of 316L stainless steel smooth substrate SSP-0 is the lowest, which is 179.135KΩ·cm 2 The polarization resistance of the superhydrophobic sample 5-0.05 is the highest, which is 405.91 KΩ·cm 2 In addition, the corrosion inhibition rate can be calculated by the following equation:
[0126]
[0127] In the formula, and j corr Refers to the corrosion current density of the treated and untreated sample surfaces. According to the corrosion inhibition rate calculation formula, the corrosion inhibition rate of the super-hydrophobic sample 5-0.05 is 58.4%. Figure f is a SEM image of the 316L stainless steel smooth substrate SSP-0 and the super-hydrophobic sample 5-0.05 after potentiodynamic polarization experiment. It can be seen from the figure that the surface morphology of the super-hydrophobic sample 5-0.05 has no obvious change, and the surface of the smooth substrate SSP-0 is corroded, and pits of different sizes appear on the surface. It can be concluded that the super-hydrophobic sample 5-0.05 can effectively prevent the underlying substrate from being corroded and has a higher corrosion resistance potential than the smooth substrate.
[0128] Table 4 Potential electrokinetic results and corrosion inhibition rates of smooth substrates and superhydrophobic samples in 3.5wt% NaCl solution
[0129] sample <![CDATA[E corr (V)]]> <![CDATA[J corr (A·cm -2 )]]> <![CDATA[β a (V)]]> <![CDATA[β c (V)]]> <![CDATA[R p (KΩ·cm 2 )]]> <![CDATA[η p ]]> Smooth substrate -0.3 <![CDATA[1.969×10 -7 ]]> 0.382 0.103 179.135 - 5-0.05 -0.161 <![CDATA[8.191×10 -8 ]]> 0.28 0.105 405.91 58.4%
[0130] 6. Simulation Application
[0131] Figure 5 (a) is a hydrogen fuel cell assembled by laser etching super-hydrophobic 316L metal bipolar plates, which mainly include metal bipolar plates, flow channel plates and membrane electrode (MEA). In order to more intuitively observe the effect of laser etching 316L stainless steel super-hydrophobic metal bipolar plates on the water management performance of hydrogen fuel cells, a bipolar plate water flow visualization observation platform was built, such as Figure 5 As shown in (b), it includes an air compressor, a water bath, a beaker, and a half-electrode assembled using a laser-etched 316L stainless steel super-hydrophobic metal bipolar plate. Hydrogen fuel cells have a wide operating temperature range (-15 to 85°C). The normal and low temperature operating conditions of hydrogen fuel cells are simulated to test the water distribution in the flow channel of the super-hydrophobic metal bipolar plate. The hydrogen fuel cell half-electrode assembled with the super-hydrophobic 316L stainless steel metal bipolar plate is the experimental group, and the hydrogen fuel cell half-electrode assembled with the smooth substrate 316L stainless steel metal bipolar plate is the control group. The results are shown in Figure 5 (c)- Figure 5 as shown in (d).
[0132] Simulate the normal temperature working condition of hydrogen fuel cells and conduct a flood proof test on the half-electrode of hydrogen fuel cells. Put deionized water into a beaker and put it into a water bath. Heat the water bath to 70°C and connect the air compressor to allow moist high-temperature air to pass through the half-electrode of the hydrogen fuel cell. The temperature of the half-electrode is kept consistent with the room temperature. Figure 5From the results (c), it can be seen that when a relatively high temperature and humid gas is passed into the half-electrode assembled with the smooth substrate SSP-0, water begins to accumulate in the flow channel within 0-300 seconds, and the water accumulation is serious at the corners of the flow channel; when a high temperature and humid gas is passed into the hydrogen fuel cell half-electrode assembled with the superhydrophobic sample 5-0.05, condensation occurs to produce water droplets when the high temperature and humid gas encounters the low temperature plate within 0-300 seconds, but because its surface is superhydrophobic, the water droplets will be blown out of the flow channel with the airflow, so there is no obvious water accumulation in the flow channel, thereby preventing the occurrence of water flooding in hydrogen fuel cells under high current density conditions.
[0133] To simulate the low temperature working conditions of hydrogen fuel cells, conduct frost protection test on half electrodes of hydrogen fuel cells. Put deionized water into a beaker and put it into a water bath. Heat the water bath to 40℃ and connect the air compressor to let room temperature humid air pass through the half electrodes of hydrogen fuel cells. The half electrodes are placed on a semiconductor refrigeration plate to keep the sample temperature at -10±2℃. Figure 5 (d) The results show that when the half-electrode assembled with the smooth substrate SSP-0 is passed into the room temperature humid gas, water begins to accumulate in the flow channel within 0-300s, and the water accumulation is serious at the corner of the flow channel; when the half-electrode assembled with the superhydrophobic sample 5-0.05 is passed into the room temperature humid gas, within 0-300s, when the humid steam encounters the low temperature plate, the humid steam condenses to produce water droplets, but because of its superhydrophobic surface, there is no obvious water accumulation and water droplet freezing in the flow channel. Therefore, the half-electrode assembled with the superhydrophobic metal bipolar plate sample has excellent anti-frost performance than the half-electrode assembled with the smooth substrate.
[0134] In summary, the present invention successfully prepared a multi-level rough super-hydrophobic surface of a 316L stainless steel metal bipolar plate by a nanosecond infrared laser fiber machine, and systematically studied its microstructure, wettability, anti-frost / icing, corrosion resistance, conductivity and drainage performance. The laser-etched pattern made on the surface of 316L stainless steel shows an ideal multi-peak surface morphology, and becomes super-hydrophobic after chemical modification. The laser-etched super-hydrophobic surface exhibits excellent anti-icing and anti-frost properties, and can still maintain good hydrophobic properties within -15 to 85°C. Even after freezing, the contact angle does not change much, which can effectively improve the cold start performance of hydrogen fuel cells and reduce the regional range restrictions on the use of hydrogen fuel cells. The laser-etched super-hydrophobic surface has excellent conductivity and corrosion resistance, both of which can meet the U.S. Department of Energy (DOE) 2025 requirements for the performance of hydrogen fuel cell bipolar plates. The laser-etched superhydrophobic surface has good drainage performance. Under the simulated normal and low temperature operating conditions of hydrogen fuel cells, there is no obvious water accumulation and water freezing in the half-electrode flow channel assembled with superhydrophobic metal bipolar plates, which improves the drainage performance of hydrogen fuel cells, effectively avoids the occurrence of "flooding" under high current density, and enhances the output performance and service life of hydrogen fuel cells.
[0135] Although preferred embodiments of the present invention have been described, additional changes and modifications may occur to these embodiments once those skilled in the art are aware of the basic inventive concepts.
[0136] Obviously, those skilled in the art may make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.
Claims
1. A method for preparing a super-hydrophobic surface on a hydrogen fuel cell bipolar plate, characterized in that: The steps include: Pretreatment of stainless steel plate: Use stainless steel plate as substrate, polish the surface with sandpaper, then ultrasonically clean it in deionized water for 10min to 15min, then ultrasonically clean it in ethanol for 10min to 15min, and after drying, obtain a stainless steel plate with a smooth surface for standby use; Nanosecond laser etching of multi-level rough surface: Use nanosecond infrared laser to process and etch patterns in the horizontal and vertical directions on the smooth stainless steel plate, ultrasonically clean it, and then soak it in stearic acid ethanol solution for 4h to 5h, and then dry it to obtain a stainless steel material with a super-hydrophobic surface; The laser parameters are set as follows: the laser scanning speed is 180 mm·s -1 ~200mm·s -1 The laser repetition frequency is 15kHz~20kHz, and the average output power is 30W~35W.
2. The method for preparing a super-hydrophobic surface on a hydrogen fuel cell bipolar plate according to claim 1, characterized in that: The sandpaper polishing process is as follows: polishing the surface of the stainless steel plate with 400#, 600#, 800# and 1000# sandpapers in sequence.
3. The method for preparing a super-hydrophobic surface on a hydrogen fuel cell bipolar plate according to claim 1, characterized in that: The drying parameters of the pretreatment process of the stainless steel plate are: drying at 80°C to 85°C for 9min to 10min.
4. The method for preparing a super-hydrophobic surface on a hydrogen fuel cell bipolar plate according to claim 1, characterized in that: The laser scanning speed, laser repetition frequency and average output power were set to 200 mm·s -1 , 20kHz and 30W.
5. The method for preparing a super-hydrophobic surface on a hydrogen fuel cell bipolar plate according to claim 1, characterized in that: The ultrasonic cleaning process after nanosecond laser etching of the multi-level rough surface is as follows: ultrasonic cleaning in deionized water for 10 min to 15 min, and then ultrasonic cleaning in ethanol for 10 min to 15 min.
6. The method for preparing a super-hydrophobic surface on a hydrogen fuel cell bipolar plate according to claim 1, characterized in that: 1.0wt% to 2.0wt% of the stearic acid ethanol solution.
7. The method for preparing a super-hydrophobic surface on a hydrogen fuel cell bipolar plate according to claim 1, characterized in that: The drying process after nanosecond laser etching of the multi-level rough surface is: drying at 80°C to 85°C for 30min to 40min.
8. The method for preparing a super-hydrophobic surface on a hydrogen fuel cell bipolar plate according to claim 1, characterized in that: The parameters for equally spaced etching patterns in the horizontal and vertical directions on a stainless steel plate with a smooth surface are as follows: the marking interval is 0.03 mm to 0.09 mm, the pattern center point interval is 0.03 mm to 0.09 mm, and the number of repeated processing times is 1 to 7 times.
9. The method for preparing a super-hydrophobic surface on a hydrogen fuel cell bipolar plate according to claim 1, characterized in that: The super hydrophobic surface presents a multi-peak rough structure with pores and nipple-like island structures on a micrometer or nanometer scale.
10. The method for preparing a super-hydrophobic surface on a hydrogen fuel cell bipolar plate according to claim 1, characterized in that: The super-hydrophobic surface is used to prepare the metal bipolar plate in the hydrogen fuel cell, thereby improving the conductivity, corrosion resistance and frost resistance of the electrode.
Citation Information
Cited By
Fuel cell stack cold start method, device, system and equipment and vehicle
CN120878894A
